The Legal Culture in The Distribution of Heritage Property Among The Muslim Community in Karas Kepoh Village, Pancur District, Rembang, Central Java - Supriyadi, Supriyadi; Ahamed, Forbis (al-'adalah, 2021)
This study aims to reveal the legal cultural background of the community in the distribution of inheritance in the village of Karas Kepoh, Pancur sub-district, Rembang district. All members of the village community can be said to have embraced Islam so that, theoretically, the community should follow Islamic law in the distribution of inheritance. In reality, however, they use the provisions in the Civil Code. This study uses a socio-legal research approach which is analyzed qualitatively. The results of the study indicate that several things underlie the legal culture of the community in the distribution of inheritance. First, the long history of Dutch colonialism which only knows the Civil Code (Burgerlijk Wet Boek). Second, almost all community members study in general education, only very few residents attend Islamic boarding schools. As a result, there are almost no community leaders or religious leaders who understand Islamic inheritance law (farâids). Thirds, village leaders in the past only justified or legalized the distribution of inheritance based on the Civil Code. Such things encourage the formation of an inheritance tradition that is not based on the provisions of Islamic law, but on the Civil Code instead. The tradition, then, turn out to be a culture that is then passed from a generation to the next generation.